(ENT300) Fundamentals Of Entrepreneurship : DELIA Handbag / Nur Dalila Ramli - Ramli, Nur Dalila (2020)
DELIA Handbag represent brand by using the trade name which are ‘DELIA’. Brand is important for us because it can express the positive emotion and image of our brand to customers. Sometimes, customer buy a product because of the brand name. So, we choose an exclusive name to make our brand same level as huge fashion brand and hope our brand will expand to the international market.